2016
DOI: 10.1149/2.0371609jss
|View full text |Cite
|
Sign up to set email alerts
|

Minority Carrier Recombination Properties of Crystalline Defect on Silicon Surface Induced by Plasma Enhanced Chemical Vapor Deposition

Abstract: This research investigates the carrier recombination properties of a crystalline defect layer introduced by the plasma enhanced chemical vapor deposition (PECVD) process of amorphous hydrogenated silicon nitride (SiNx) passivation films. A direct PECVD technique was used for SiNx films deposition. A crystalline defect layer existed on the surface of the silicon substrate and is under the SiNx passivation film. The recombination lifetime in this defect layer was obtained by focusing on the thickness of the defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…To avoid carrier recombination at defects and improve minority carrier lifetimes, the cell surfaces are generally passivated using dielectric layers, such as hydrogenated silicon nitride (Si x N y :H) and/or silicon dioxide (SiO 2 ). However, UV exposure can disrupt this surface passivation by damaging the passivation layer itself or the passivation layer/Si cell interface 11–14 as well as causing subsurface damage in the silicon 15,16 . Different research groups have identified distinct wavelengths in the 300–400 nm spectral range as the damaging wavelengths of incident radiation for UV degradation of Si solar cells 13,14,17–24 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…To avoid carrier recombination at defects and improve minority carrier lifetimes, the cell surfaces are generally passivated using dielectric layers, such as hydrogenated silicon nitride (Si x N y :H) and/or silicon dioxide (SiO 2 ). However, UV exposure can disrupt this surface passivation by damaging the passivation layer itself or the passivation layer/Si cell interface 11–14 as well as causing subsurface damage in the silicon 15,16 . Different research groups have identified distinct wavelengths in the 300–400 nm spectral range as the damaging wavelengths of incident radiation for UV degradation of Si solar cells 13,14,17–24 …”
Section: Introductionmentioning
confidence: 99%
“…However, the recombination velocity at this region is increased by the UV irradiation, resulting in a decrease in carrier lifetime. Another paper revealed that subsequent etching and removal of the damaged passivation and defect layer tend to recover the carrier lifetime 16 . Further, the defects in the damaged layer were electrically inactivated due to high‐temperature annealing (600°C) and thereby resulting increase in the effective lifetime 32…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the parametrization of Auger in the simulations can affect the shape of the curve. 18 Furthermore, it must be noted that the simulation structure has not implemented a damaged layer at the interfaces 19 and that the surface recombination model is based on SRH for a mid-gap single level defect. The simplification of the simulation model can also affect the shape of the curves.…”
Section: -3mentioning
confidence: 99%